2008
DOI: 10.1287/isre.1080.0193
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Reviews and Sales: The Role of Reviewer Identity Disclosure in Electronic Markets

Abstract: C onsumer-generated product reviews have proliferated online, driven by the notion that consumers' decision to purchase or not purchase a product is based on the positive or negative information about that product they obtain from fellow consumers. Using research on information processing as a foundation, we suggest that in the context of an online community, reviewer disclosure of identity-descriptive information is used by consumers to supplement or replace product information when making purchase decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
828
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 1,322 publications
(916 citation statements)
references
References 62 publications
28
828
3
6
Order By: Relevance
“…Clemons, Gao, and Hitt (2006) showed that not only the variance of ratings but also the strength of the most positive quartile of reviews has a significant impact on the growth of craft beers. In addition to the features of online reviews, the effect of the degree to which review writers disclose their identity in the evaluation of product quality and product sales has been discussed (e.g., Forman, et al, 2008). While a number of researchers have concluded that an improvement in the review score leads to an increase in relative sales online, Chen and Wu (2005) and Duan et al (2008) demonstrated that high product ratings do not necessarily lead to increased sales.…”
Section: Online Consumer Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clemons, Gao, and Hitt (2006) showed that not only the variance of ratings but also the strength of the most positive quartile of reviews has a significant impact on the growth of craft beers. In addition to the features of online reviews, the effect of the degree to which review writers disclose their identity in the evaluation of product quality and product sales has been discussed (e.g., Forman, et al, 2008). While a number of researchers have concluded that an improvement in the review score leads to an increase in relative sales online, Chen and Wu (2005) and Duan et al (2008) demonstrated that high product ratings do not necessarily lead to increased sales.…”
Section: Online Consumer Reviewsmentioning
confidence: 99%
“…Fogg et al (2001) demonstrated that reviewers' names and photos in the online information source have a positive relationship with people's perception of the credibility of websites on the basis of the information processing theory (Mackie, Worth & Asuncion, 1990). Forman, et al (2008) pointed out that message recipients may use the personal information of the message creator as a heuristic cue, drawing on the evaluation of the information provider as a cognitive device to assist them to reach judgements and actions.…”
Section: Reviewers' Identity Disclosurementioning
confidence: 99%
See 3 more Smart Citations